Learning Goals Achievement of a Teacher in Professional Development - Siti Marfu’ah; Istanto Wahyu Djatmiko; Moh. Khairudin (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
This study aimed to describe the achievement of teacher learning in cognitive, affective and psychomotor in conducting professional development. This study was categorized as a descriptive study. The respondents of this study were teachers and students in the Department of Electrical Engineering at a Vocational Secondary School in Bangka Belitung. Methods of data collection used questionnaires. The data were analyzed with descriptive analysis. The results of this study consisted of: (1) teachers’ opinion, most teachers had worked very well in learning of cognitive, affective, and psychomotor, (2) students’ opinion, several teachers had succeeded in cognitive learning, and managed very well on affective and psychomotor learning.